Program Sekolah dalam Upaya Pencegahan NAPZA - Fidrayani Fidrayani; Desiana Utami (Jurnal Harkat : Media Komunikasi Gender, 2018)
Abstract. Narcotics in unattended use can have a negative impact. The impact is potential to destroy the youth generation. It is necessary to hold the drug prevention programs, especially in schools as one of ways to prevent the widespread negative impact. The prevention can be through the role of parents, teachers and stakeholders as part of the community. The teachers’ role is divided into four sub-role, namely as educators, as advisors, as mentors, and particularly as problem solvers. The role of teachers certainly will not have power if it is not supported by the role of schools. Effots that are conducted by school stakeholder are as follow: a) compose the school rules; b) conduct inspections intensively and spontaneously; c) cooperate with related institutions for counseling and socialization; d) utilize extracurricular activities as means of prevention; e) integrate drug awareness into learning curriculum; (f) maximize the tasks as the effort of drug abuse prevention. Expectedly, these drug prevention efforts can be implemented by all schools as one of ways to prevent the destruction of the nation through NAPZA. Abstrak. Narkoba dalam penggunaan yang tidak diawasi dapat menimbulkan dampak negatif. Dampak tersebut tidak menutup kemungkinan dapat merusak generasi muda. Salah satu cara agar bahaya tersebut tidak meluas dampaknya, maka perlu program pencegahan terutama di sekolah. Pencegahan tersebut dapat melalui peran orang tua, guru dan pemangku kebijakan sebagai bagian dari masyarakat. Peran guru dibagi dalam empat yakni sebagai pendidik, penasehati, pembimbing dan lebih utama lagi sebagai problem solver. Peran guru ini tentu tidak akan memiliki kekuatan jika tidak didukung oleh peran sekolah. Upaya yang dilakukan oleh pihak sekolah adalah a) membuat tata tertib sekolah, b) melakukan razia intensif dan spontan, c) bekerjasama dengan instansi terkait guna penyuluhan dan sosialisasi, d) menggunakan ekstrakurikuler sebagai sarana pencegahan, e) memasukkan materi tentang narkotika ke dalam kurikulum pengajaran, f) memaksimalkan tugas dalam upaya pencegahan penyalahgunaan NAPZA. Diharapkan agar upaya pencegahan tersebut dapat diikuti oleh semua sekolah sebagai salah satu usaha untuk mencegah rusaknya anak bangsa melalui NAPZA.